Promotion of Brahmi (Bacopa monniera) Growth by Cyanobacterium Nostoc sp. Extract - Laloknam, Surasak; Tengnoy, Salinee; Kaewkham, Waranya; Bualuang, Aporn; Boonburapong*, Bongkoj (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Bacopa monniera (Brahmi), a saponin-containing medicinal and culinary herb, can be used to enhance memory and rejuvenate the brain. Moreover, it has other human health benefits. The cyanobacterium Nostoc sp. has been shown to produce bioactive compounds and plant growth regulators like indol acetic acid (IAA), which regulates various aspects of plant growth and development. This research aimed to study the effects of Nostoc sp. extract (NTE) supplement concentration in liquid medium on Brahmi survival rate, growth parameters, and saponin content. The experiments were designed using randomized complete block design with five treatments and three replications, including Bristol’s medium (BT), pH 6.0 (control solution), and BT with four concentrations of NTE: 0.001, 0.01, 0.1, and 1.0%(w/v). The results indicated that IAA was found to increase with increase in NTE concentration. The IAA concentration in 1.0%(w/v) NTE was 43.56±3.21 pmol.mg-1 Ch-a. NTE supplementation at 0.001%, and 0.01%(w/v) had no negative effect on Brahmi survival rate, while the Brahmi survival rate decreased with increase in NTE concentration up to 0.1% (w/v). The optimal NTE concentration for Brahmi growth was 0.01%(w/v), which produced the highest shoot number, shoot height, root number, root length, leaf number, and chlorophyll content. Brahmi grown under all treatments was extracted and determined for the saponin content. The results showed that the levels of saponin from Brahmi grown in 0.01%(w/v) NTE had increased by two-fold over the control. This study showed that NTE supplementation enhanced the growth and saponin levels of Brahmi and NTE could be used as bio-promoting agent for plant growth and development. Keywords: Nostoc; Brahmi; growth; IAA; saponin *Corresponding author: Tel.: (+66) 806944514 E-mail: bongkoj@g.swu.ac.th